Transcriptional transitions in Nicotiana benthamiana leaves upon induction of oil synthesis by WRINKLED1 homologs from diverse species and tissues - Grimberg, Åsa (BMC Plant Biol, 2015)
BACKGROUND: Carbon accumulation and remobilization are essential mechanisms in plants to ensure energy transfer between plant tissues with different functions or metabolic needs and to support new generations. Knowledge about the regulation of carbon allocation into oil (triacylglycerol) in plant storage tissue can be of great economic and environmental importance for developing new high-yielding oil crops. Here, the effect on global gene expression as well as on physiological changes in leaves transiently expressing five homologs of the transcription factor WRINKLED1 (WRI1) originating from diverse species and tissues; Arabidopsis thaliana and potato (Solanum tuberosum) seed embryo, poplar (Populus trichocarpa) stem cambium, oat (Avena sativa) grain endosperm, and nutsedge (Cyperus esculentus) tuber parenchyma, were studied by agroinfiltration in Nicotiana benthamiana. RESULTS: All WRI1 homologs induced oil accumulation when expressed in leaf tissue. Transcriptome sequencing revealed that all homologs induced the same general patterns with a drastic shift in gene expression profiles of leaves from that of a typical source tissue to a source-limited sink-like tissue: Transcripts encoding enzymes for plastid uptake and metabolism of phosphoenolpyruvate, fatty acid and oil biosynthesis were up-regulated, as were also transcripts encoding starch degradation. Transcripts encoding enzymes in photosynthesis and starch synthesis were instead down-regulated. Moreover, transcripts representing fatty acid degradation were up-regulated indicating that fatty acids might be degraded to feed the increased need to channel carbons into fatty acid synthesis creating a futile cycle. RT-qPCR analysis of leaves expressing Arabidopsis WRI1 showed the temporal trends of transcripts selected as ‘markers’ for key metabolic pathways one to five days after agroinfiltration. Chlorophyll fluorescence measurements of leaves expressing Arabidopsis WRI1 showed a significant decrease in photosynthesis, even though effect on starch content could not be observed. CONCLUSIONS: This data gives for the first time a general view on the transcriptional transitions in leaf tissue upon induction of oil synthesis by WRI1. This yields important information about what effects WRI1 may exert on global gene expression during seed and embryo development. The results suggest why high oil content in leaf tissue cannot be achieved by solely transcriptional activation by WRI1, which can be essential knowledge in the development of new high-yielding oil crops. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-015-0579-1) contains supplementary material, which is available to authorized users.